Modelling the ingress of a temperate fish larva into a nursery coastal lagoon. (5th April 2020) - Baptista, Vânia; Leitão, Francisco; Morais, Pedro; Teodósio, Maria Alexandra; Wolanski, Eric
Abstract: The development of sensorial acuity and swimming capabilities of coastal fish larvae and their responses to coastal nursery cues are essential for recruitment success. Most studies of the response of fish larvae to environmental cues and their recruitment into nursery areas have focused on coral reef fish and only a few studies focused on fish species from temperate regions. The Sense Acuity and Behavioural (SAAB) Hypothesis proposes that fish larvae in temperate regions can sense nursery cues and ingress into estuarine ecosystems by using several active swimming strategies. We tested the SAAB hypothesis by studying the ingress of a temperate fish larvae – white seabream Diplodus sargus (Linnaeus, 1758) – into a coastal nursery area, the Ria Formosa Lagoon, Portugal. We combined the results from studies of sensory acuity, swimming capabilities and personality traits of post-flexion larvae with a fine-scale biophysical model to quantify the ingress of the white seabream into the lagoon. Data showed that the location of spawning sites and the directional swimming capabilities are both important for the successful ingress of white seabream larvae into the lagoon. Recruitment was higher when spawning grounds were located in areas with depths between 15.1 and 16.9 m and when post-flexion larvae used their directional swimming capabilities. The larvae ingressed passively into the lagoon with the tidal currents at pre-flexion stage and actively by using their directional swimming capabilities at post-flexion stage. Directional swimming also prevented larval export into the coastal area. When spawning occurred away from the seagrass smell plume emanating from the lagoon, the fish larvae were advected away and lost at sea. This work demonstrated the relevance of combining fish larvae behaviour and oceanography processes in modelling the dispersion of fish larvae to estimate recruitment. Highlights: Spawning location (distance from the coast and depth) influences the ingress of larvae into the nursery area. Presence and detection of estuarine smell plumes increase the ingress of larvae into the nursery area. Directional swimming capabilities of post-flexion larvae increase their ingress into the nursery area. Directional swimming prevented the export of larvae from the nursery area.